Consumer characteristics and their effect on accepting online shopping, in the context of different product types - Ellisavet Keisidou; Lazaros Sarigiannidis; Dimitrios Maditinos (International Journal of Business Science & Applied Management (IJBSAM), 2011)
Online shopping is among the most popular activities of the internet, yet the reasons why consumers buy online are still unclear. Although it is implied that consumer acceptance of online shopping is affected by different products not many studies have adopted this view. This study attempts to examine consumers' attitude when making online purchases in the context of different product types. A theoretical framework is proposed based on the determinants of consumer behaviour and user acceptance of online shopping, as well as online product classification. The factors that were selected to be tested are Personal Innovativeness of Information Technology (PIIT), Self-efficacy, Perceived security, Privacy, Product involvement and how they affect consumer attitude towards online shopping. Correlation analysis, at first, to determine the relationships among the variables and regression analysis afterwards to verify the extent of the variable interaction were used to test the hypotheses. Based on the aforementioned analyses, results were drawn and compared to the results found by Lian and Lin (2008) in a similar study. It has been found that PIIT, perceived security and product involvement have an effect on the attitude towards online shopping, yet the results vary among the different product types.
Keywords: 650; personal innovativeness of information technology (PIIT); self-efficacy; perceived security; privacy concerns; product involvement